Effect of sesame oil, ozonated sesame oil, and chlorhexidine mouthwash on oral health status of adolescents: A randomized controlled pilot trial - V Chitra Vadhana; Asokan Sharath; P R Geethapriya; V Vijayasankari (Wolters Kluwer Medknow Publications, 2019)
Context: Oil pulling procedure involves swishing of oil in the mouth for various oral health benefits. Aim: The aim of the study was to evaluate the effectiveness of sesame oil (SO), ozonated SO (OSO), and chlorhexidine (CHX) mouthwash on the oral health status of adolescents. Study Settings and Design: Parallel multi-arm double-blinded randomized trial was done in a Government higher secondary school. Materials and Methods: A total of 75 adolescents aged 12-14 years with decay-missing-filled index ≤3 were randomly assigned to three groups (n = 25): Group I (SO), Group II (OSO), and Group III (CHX mouthwash). Baseline (T1) Debris Index (DI-S), Calculus Index (CI-S), Oral Hygiene Index-Simplified (OHI-S), Plaque Index (PI), and salivary Streptococcus mutans count were recorded. All the groups were subjected to intervention with the respective mouth rinses for 15 days. The index scores and the salivary S. mutans count were reassessed after 15 days (T2) and 1 month (T3), and the results were statistically analyzed. Statistical Analysis: The statistical analysis was done using IBM SPSS Statistics for Windows. The statistical significance was set at P ≤ 0.05. Kolmogorov-Smirnov and Shapiro-Wilk test were used to test the normality of the data. The Friedman test and Wilcoxon-signed rank test were carried out for intragroup comparison. Kruskal-Wallis and Mann-Whitney U-test were employed to analyze inter-group comparison. Results: All the groups showed statistically significant reduction in DI-S, CI-S, OHI-S, PI, and S. mutans count after 15 days. Conclusion: Oil pulling therapy using SO and OSO showed a significant improvement in oral hygiene.